PROFESSIONAL TRAINING OF TEACNERS THROUGH DISTANCE LEARNING IN THE REPUBLIC OF CYPRUS - Voyevutko, Natalya (Continuing Professional Education: Theory and Practice, 2019)
The article analyses the content of professional training of teachers through distance learning in the Republic of Cyprus. The study shows that nowadays there are seven public and private universities in the country, six of them provide pedagogical education. The University of Cyprus boasts of the largest range of pedagogical specialties at the Bachelor, Master and Doctoral levels. However, pedagogical education is not delivered through distance learning in the abovementioned institution of higher education. In contrast to public universities, private institutions of Cyprus offer diversification of programs related to pedagogical education. FrederickUniversity provides the widest spectrum of distance education programs at the Master educational level. The author specifies that unlike the other universities of Cyprus offering specialized programs aimed at learning a particular subject, the University of Nicosia one program «Pedagogical Sciences» comprising a range of specializations, namely, educational leadership and administration; special needs education and training; teaching music; art and education; theory, practice and evaluation of teaching; education techniques; teaching Mathematics and natural sciences; teaching language and literature. This program is the only one in Cyprus recognized by the Ministry of Education, Research and Religious Affairs of Greece and the University of Nicosia is the only educational institution of Cyprus recognized and certified by the European Foundation for Quality in eLearning. The article describes the procedure of admission to PhD programs related to pedagogy. The author gives the details of the content of the most popular Master programs: «Pedagogical Education», «Continuous Education and Lifelong Learning», «Special Needs (Inclusive) Education», «Educational Management», «Educational Leadership». The study outlines the features of organization of pedagogical practice through distance learning. The author highlights the positive developments of the Republic of Cyprus in the diversification of educational programs related to pedagogy.